PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN SPIRITUAL TERHADAP KINERJA GURU - Sonitra Sonitra; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This is a survey research with a quantitative approach based on the importance of teacher performance in a school. This study aims to analyze the effect of Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence on Teacher Performance. The object of this research is the teacher in the district of South Bengkulu, Pino. The number of respondents in this study was 131 people. The data collection method uses a questionnaire. The results of this study can be concluded that the intellectual intelligence variable has a significant effect on Teacher Performance, Emotional Intelligence has a significant effect on Teacher Performance and Spiritual Intelligence has a significant effect on Teacher Performance